PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN CIMANGGU KABUPATEN PANDEGLANG - Novia Oktaviani; Muhamad Guruh (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of Work Discipline and Work Motivation on employee performance at the cimanggu sub-district office, pandeglang district. The method used is quantitative analysis method, which uses in-depth data in the form of numbers. The sampling technique uses saturated sampling which takes the entire population to be sampled, the sample in this study were 62 respondents. Data analysis using descriptive data analysis, with validity test, reliability test, classical assumption test with normality test, multicollinearity test, auto correlation test, heteroscedasticity test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing with t test and f test. The results showed that Work Discipline has a statistical effect on employee performance but is not unidirectional, which means that the opposite effect is the difference between the impact of Work Discipline and Work Motivation on employee performance. With the value of the regression equation Y = 75.343 + -.1064X1. The coefficient of determination is 42.2%. hypothesis testing in the t test count> t table or (6.619> 1.670). Work Motivation has a positive and significant effect on employee performance with a regression equation value of Y = 29.7767 = 0.943X2. The coefficient of determination is 38.1%. hypothesis testing in the t test count> t table or (6,076> 1,670).